Shift working and trade in labor services with time zone differences - Toru Kikuchi; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2011)
Using a two-factor (labor and capital), two-good (shift-working and non shiftworking commodities) model with two countries (Home and Foreign) which are located in different time zones, we highlight the impact of trade in labor services (via communication networks) on the comparative advantage of countries capable of such trade. It is shown that a comparative advantage in the shift-working commodity is held by pairs of countries in different time zones and connected through a good communication network. Concerning factor prices, if the shiftworking commodity is capital (resp. labor) intensive, the wage rate for day-shift labor will decrease (resp. increase) as a result of trade in labor services. It is also demonstrated that this kind of labor services utilization is mutual: some of Home's day-shift labor will be utilized for Foreign night-shift, and vice versa. Thus, periodic trade in labor services occurs across countries.
Keywords: F16; 330; shiftworking; time zones; trade in labor services; Internationaler Dienstleistungsverkehr; Lohnfertigung; Zeit; Internet; Komparativer Kostenvorteil; Globalisierung; Theorie